CRYPTOCURRENCY ADOPTION ENHANCES FINANCIAL INCLUSION MEDIATED BY USER SATISFACTION AND PERCEIVED ECONOMIC EMPOWERMENT IN INDONESIA - Ferli, Ossi; Gonardo, Dylan; Dava , Gabriel Radja; Yasin, Muhammad (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Financial inclusion remains a significant challenge in developing countries, where over 1.7 billion people lack access to bank accounts due to high costs, limited infrastructure, and a lack of formal identification. As a result, many rely on insecure informal systems, which results in user dissatisfaction in the long run. Cryptocurrencies like Bitcoin, powered by blockchain technology, offer a promising alternative by enabling fast, low-cost, and highly secure transactions without the need for traditional banking institutions. This study empirically investigates how cryptocurrency adoption can enhance financial inclusion in Indonesia, both directly and indirectly through mediating factors such as user satisfaction, trust in financial institutions, and perceived economic empowerment. The study explores whether cryptocurrency use fosters financial autonomy, strengthens trust in digital financial services, and increases satisfaction with financial technologies—factors that may encourage broader participation in the formal financial system. Data were collected through a Google Form survey involving 147 respondents, Indonesian cryptocurrency investors. Using Partial Least Squares (PLS) analysis, results reveal that while cryptocurrency adoption significantly improves user satisfaction, trust in the financial system, and economic empowerment, with scores of 0.888, 0.732, and 0.851, respectively. Cryptocurrency adoption also has a direct effect on financial inclusion, with a score of 0.635. However, perceived economic empowerment emerged as a strong mediating variable, with a score of 0.556 to financial inclusion, compared to user satisfaction with a mediating score of 0.282 to financial inclusion. These findings highlight that high economic empowerment is a key value driver for crypto investors. The results show platforms emphasizing accessibility, security, and transparency may be better positioned to support financial inclusion in emerging economies like Indonesia, without having to engage in a formal financial system. JEL Classification Codes: D53, E22, E42, G41.